Cardiometabolic biomarkers and systemic inflammation in us adolescents and young adults with latent tuberculosis infection: a population-based cohort study - Magodoro,IM; Ntusi,NAB; Jao,J; Zar,HJ; Claggett,BL; Siedner,MJ; Wilkinson,KA; Wilkinson,RJ (Open Forum Infectious Diseases, 2025)
BackgroundMycobacterium tuberculosis (Mtb) infection in adults increases incident type 2 diabetes and atherosclerotic cardiovascular disease risk. It is unknown if this cardiometabolic detriment occurs in young people. We investigated whether young persons with latent tuberculosis infection (LTBI) have worse cardiometabolic health than their peers who are uninfected.MethodsPeripubescent adolescents (12–15 years old) and older adolescents/young adults (16–30 years old) were assessed for LTBI by tuberculin skin testing (induration ≥10mm). Outcomes included fasting plasma glucose, hemoglobin A1c, C-peptide, N-terminal prohormone of brain natriuretic peptide, high-sensitivity cardiac troponin T, C-reactive protein, ferritin, diabetes/prediabetes (fasting plasma glucose ≥5.6mmol/L and/or hemoglobin A1c ≥5.7%), and homeostatic model of insulin resistance. LTBI cases were propensity score matched 1:4 with controls who were uninfected with tuberculosis (TB) on sociodemographics to estimate adjusted median, mean difference, and odds ratio of cardiometabolic indices.ResultsSeventy-five LTBI cases were matched to 300 peers who were TB uninfected. Among older participants, LTBI was associated with higher inflammation (adjusted median [IQR]: C-reactive protein, 0.22 mg/dL [0.05–0.34] vs 0.11 [0.04–0.35], P = .027; ferritin, 55.0 ng/mL [25.1–90.3] vs 41.1 [29.5–136.2], P = .047) but not among peripubescent adolescents. No meaningful differences were observed in fasting plasma glucose (adjusted mean difference [95% CI], −0.05 mmol/L [−.22 to .12]; P = .57), hemoglobin A1c (0.0% [−.17% to .17%], P = .98), diabetes/prediabetes prevalence (adjusted odds ratio [95% CI], 0.9 [.29–2.29]; P = .85), insulin secretion/resistance, N-terminal prohormone of brain natriuretic peptide, or high-sensitivity cardiac troponin T by LTBI status.ConclusionsOlder adolescents and young adults with LTBI had higher inflammation than th